ANALISIS TIPOLOGI WILAYAH DALAM MENDUKUNG PENGEMBANGAN MINAPOLITAN DI PROVINSI GORONTALO - Taslim Arifin; Terry L Kepel; Syahrial Nur Amri (TATALOKA, 2013)
Development of the region by Minapolitan approach as a fisheries development concept cannot be applied partially but should be holistic developed by developing all the availability in cities to the rural areas. This study aims to understand the structure and pattern of regional economic growth and to find out the potency and competitiveness of the area as a priority for fisheries development center in Gorontalo Province. This study uses Klassen and Shift-Share (S-S) typology analysis. Area that has the better economic structure is Pohuwato Regency. This region has Gross Regional Domestic Bruto (GRDB) per capita above the provincial value, however economic development still below the provincial level (high income but low growth) or categorized as developed region but stressed category. Boalemo Regency, Pohuwato Regency and Bone Bolango Regency have almost equal fishery development value, which are 18.6%, 16.2% and 12.7% respectively. Gorontalo Regency grow only as large as 7.4 %. This is inseparable from the production of fishery sub-sector in Gorontalo Regency that only share 8% to the fisheries production.Development of the region by Minapolitan approach as a fisheries development concept cannot be applied partially but should be holistic developed by developing all the availability in cities to the rural areas. This study aims to understand the structure and pattern of regional economic growth and to find out the potency and competitiveness of the area as a priority for fisheries development center in Gorontalo Province. This study uses Klassen and Shift-Share (S-S) typology analysis. Area that has the better economic structure is Pohuwato Regency. This region has Gross Regional Domestic Bruto (GRDB) per capita above the provincial value, however economic development still below the provincial level (high income but low growth) or categorized as developed region but stressed category. Boalemo Regency, Pohuwato Regency and Bone Bolango Regency have almost equal fishery development value, which are 18.6%, 16.2% and 12.7% respectively. Gorontalo Regency grow only as large as 7.4 %. This is inseparable from the production of fishery sub-sector in Gorontalo Regency that only share 8% to the fisheries production.